Halophytes and salt-tolerant glycophytes a potential resource - Sardo V. (The use of non conventional water resources, 2005)
Water of good quality for agricultural uses is becoming ever more limited in regions where irrigation is necessary, due to increasing requirements for domestic and industrial uses. This makes exploration of using .non conventional. waters mandatory. Seawater or saline water may be used to irrigate a variety of plants, both halophytes and glycophytes, however their use entails a number of problems. A review is given of the halophytes most commonly grown and of their various uses, of the response of some glycophytes when irrigated with saline water and of the possible levels of production. A brief account is given of researches addressing plant tolerance to various salinity levels; salt balance in the soil as affected by leaching fractions and precipitations; soil physical conditions as affected by irrigation systems.
International Workshop, 2005/06/12-14, Alger (Algeria)